Application of NCB Asset Confiscation in Handling Corruption Crimes in Indonesia - Yogi Syahputra Al idrus; Kukuh Dwi Kurniawan (Publikasi Indonesia, 2024)
Applying NCB (non-convection based not on treasury), commonly called asset confiscation punishment without punishment, is an innovative solution for appropriating corruption when a person cannot cope with criminal, civil and administrative penalties. The problem that exists all ready for change, of course, requires regulation in this regard. It is very important to look at these regulations and how a convection-based asset recovery policy is a government loss recovery policy related to state loss crimes such as corruption, money laundering, etc. Therefore, the subjects considered in this study are how NCB Asset Forfeiture is applied in dealing with criminal acts of corruption in Indonesia. This research method seeks normative law by examining secondary and qualitative data. It is from this that the first conclusion can be drawn: the urgency of implementing the NCB policy (Non-Convection based on not Forteiture) in Indonesia, namely the existence of obesity problems from state losses with massive corruption crimes that have occurred and efforts to harmonise and legitimise the NCB Draft Asset confiscation bill to overcome state losses. Second, the legal response in applying the concept of NCB (Non-Convection Based Forfeiture), namely cooperation with other countries in exploiting evil assets.